2000
DOI: 10.7863/jum.2000.19.12.807
|View full text |Cite
|
Sign up to set email alerts
|

Color Doppler sonography for evaluating response to transcatheter arterial embolization and percutaneous ethanol injection therapy and for detecting recurrence of hepatocellular carcinoma.

Abstract: Eighty-six patients (mean age, 63 years) with 92 hepatocellular carcinomas (2.0 cm or greater in diameter; mean +/- SD, 3.5 +/- 1.6 cm) underwent color Doppler sonography before and after transcatheter arterial embolization and after subsequent percutaneous ethanol injection for (1) identification of pulsatile flow in the residual tumor area after transcatheter arterial embolization, (2) evaluation of therapeutic effectiveness of combined transcatheter arterial embolization and percutaneous ethanol injection, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Therefore, other imaging modalities have been tried to establish the outcome of TACE. [9][10][11][12][13][14][15] Intratumoral vascularity after TACE has been shown to correlate with tumor viability and is used as the major criterion for additional treatment. 8 Therefore, various imaging modalities have been used to evaluate the vascularity of HCCs treated with TACE, and recently, several investigators have suggested that contrastenhanced sonography could be useful in depicting vascularity in HCCs treated with TACE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, other imaging modalities have been tried to establish the outcome of TACE. [9][10][11][12][13][14][15] Intratumoral vascularity after TACE has been shown to correlate with tumor viability and is used as the major criterion for additional treatment. 8 Therefore, various imaging modalities have been used to evaluate the vascularity of HCCs treated with TACE, and recently, several investigators have suggested that contrastenhanced sonography could be useful in depicting vascularity in HCCs treated with TACE.…”
Section: Discussionmentioning
confidence: 99%
“…8 Therefore, various imaging modalities have been used to evaluate the vascularity of HCCs treated with TACE in many studies. [9][10][11][12][13][14][15] The effectiveness of contrast-enhanced sonography in evaluating the therapeutic response of HCC treated with TACE has been advocated by several authors. [16][17][18] To our knowledge, there has been no prospective comparison of contrast-enhanced sonography and multiphasic computed tomography (CT) in evaluation of the therapeutic response of HCCs treated with TACE.…”
mentioning
confidence: 99%
“…Third, the outcome of no local recurrence in the follow-up (mean, 7.4 months) in this study may be because the follow-up was relatively short; therefore, the follow-up should be prolonged and should include careful observations. Regarding local recurrences, Shirato et al 14 and Lencioni et al 26 reported that they found 38 (41.3%) of 92 lesions and 3 (6.4%) of 47 cases, during follow-up of 3 to 45 months (mean, 12.2 months) and 2 to 78 months (mean ± SD, 22.5 ± 16.45 months), after PEI with TAE and PEI therapy only, respectively. The fourth limitation is that the depiction capability of contrast-enhanced CDS is highly susceptible to cardiac motion artifacts, although contrast-enhanced CDS has a relatively high depiction capability.…”
Section: Discussionmentioning
confidence: 99%
“…Color Doppler sonography (CDS) and power Doppler sonography are used during and after PEI and in follow-up sessions because of their ability to depict a tumor with the use of relatively portable technology. [13][14][15] The depiction of tumor vascularity plays an important role in performing PEI, because the residue of flow signal suggests incomplete ablation of the tumor. Therefore, ethanol must be injected into the tumor until the tumoral flow signal completely disappears.…”
mentioning
confidence: 99%
“…Generally it is defined by the intratumoral necrosis and the tumor mass reduction and it is assessed with dynamic CT or MRI. However, various imaging modalities have been used to evaluate the vascularity of HCCs treated with TACE [77,78] and many studies have shown the effectiveness of contrast-enhanced sonography in evaluating the therapeutic response of HCC treated with TACE [79,80]. Formally no guidelines recommend the use of CEUS to assess TACE response.…”
Section: Conventional Chemoembolization (Ctace)mentioning
confidence: 99%